Rifqi Faris Studi Literatur: Efektivitas Blended learning terhadap Minat, Motivasi, dan Hasil Belajar: Literature review: The Effectiveness of Blended Learning on Interest, Motivation, and Learning Outcomes - Rifqi Faris Azzaki; Sri Marmoah (Jurnal IKA, 2026)
Blended learning, as a combination of face-to-face and online learning, has become an important innovation in improving the quality of education. This study aims to analyze the effectiveness of Blended learning on students’ interest, motivation, and learning outcomes through a Systematic Literature Review (SLR). Articles were collected from Scopus and SINTA databases using strict inclusion–exclusion criteria with the keywords “Blended learning,” “learning interest,” “learning motivation,” and “learning outcomes.” From an initial 120 articles, 22 publications from 2018–2025 met the criteria. The analysis combined descriptive methods to map research trends by year, country, and methodology, and thematic analysis to identify key patterns and themes. The findings reveal that Blended learning effectively enhances students’ interest, intrinsic motivation, and academic achievement compared to traditional methods, particularly when supported by interactive media, formative assessment strategies, and digital technologies. However, challenges remain in terms of students’ readiness, diverse learning styles, and limited use of technology. The study concludes that the effectiveness of Blended learning depends not only on instructional design but also on supportive learning environments and teacher strategies. Practical recommendations include strengthening evidence-based instructional design, adopting adaptive technologies, and enhancing teachers’ capacity to ensure that Blended learning becomes a sustainable solution for improving educational quality.